The evaluation of teacher's helpful styles that develop thinking skills of the sixth grade students at the basic education A field study from the view point of mathematics teachers in the city of Lattakia - Ali, Khodor; Ahmad , Mutieah (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present study aimed at evaluating the styles of the mathematics teachers which help to develop thinking skills of the sixth grade students at the basic education in Lattakia, and it also aimed at examining the significance of differences among the means average of teachers who practice the encourage methods to thinking skills of students according to variables of (gender, Experience and the scientific qualification). To achieve this goal, the descriptive approach was used. And an assessment scale of the teacher's style of developing thinking was prepared for evolution. After proving its validity and stability according to the known statistical methods, the scale was applied to a sample of 30 teachers (males and females). The results were as follows: - The degree of mathematics teachers concerning their practices of developing thinking methods of the of the sixth graders at the basic education in Lattakia was (54.2%) which was represented first by providing the interactive social environment (58.4%), and second it was represented to (53.6%) for the method of listening to students and respecting their views whatever they were simple, and third it was represented to (51%) concerning the teacher' using modern to modern teaching strategies. - There are no statistical significant differences between the teachers' responses on the teacher practice scale of developing thinking methods due to the variable of gender, scientific certificate, and the years of experience. The two researchers suggested developing of the mathematics guide book of the sixth grade, and developing programs of preparing and training teachers to improve the levels of thinking by students such as analysis, synthesis, criticism and weight-bearing skills, in addition to holding training sessions to in-service teachers in order to activate the teaching practices methods that encourage developing thinking, and they also suggested applying similar studies depending on the observation card at different teaching stages by other subjects teachers.